PENGARUH MAKRO EKONOMI TERHADAP CADANGAN DEVISA DI ASEAN-5 - Soeharjoto Soekapdjo; Gandhi Kuntoyudho Danova (LPPM Universitas BSI, 2020)
In supporting economic development in ASEAN-5, foreign exchange reserves have a large role. Macroeconomic changes will have a large and rapid impact on foreign exchange reserves at globalization era. . Aims of this study is to determine the effect of macroeconomics on foreign exchange reserves in ASEAN-5, using panel data regression method. Data is taken from world banks and Banks Indonesia quarterly from 2010-2018, with dependent variables on foreign exchange reserves and independent variables in the form of exchange rates, inflation, exports and imports. Results shown that exchange rates and exports have a positive and significant effect on foreign exchange reserves, while inflation has a negative and significant effect on foreign exchange reserves, but imports do not affect at foreign exchange reserves in ASEAN-5. Government needs maintain exchange rate stability, inflation, and increase foreign investors and domestic commodities by using local content. Entrepreneurs must strive to continue to innovate by using digital technology and society to increase the use of domestic products.